-(2x+3)-5(x-2)=2x-7

Simple and best practice solution for -(2x+3)-5(x-2)=2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(2x+3)-5(x-2)=2x-7 equation:


Simplifying
-1(2x + 3) + -5(x + -2) = 2x + -7

Reorder the terms:
-1(3 + 2x) + -5(x + -2) = 2x + -7
(3 * -1 + 2x * -1) + -5(x + -2) = 2x + -7
(-3 + -2x) + -5(x + -2) = 2x + -7

Reorder the terms:
-3 + -2x + -5(-2 + x) = 2x + -7
-3 + -2x + (-2 * -5 + x * -5) = 2x + -7
-3 + -2x + (10 + -5x) = 2x + -7

Reorder the terms:
-3 + 10 + -2x + -5x = 2x + -7

Combine like terms: -3 + 10 = 7
7 + -2x + -5x = 2x + -7

Combine like terms: -2x + -5x = -7x
7 + -7x = 2x + -7

Reorder the terms:
7 + -7x = -7 + 2x

Solving
7 + -7x = -7 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
7 + -7x + -2x = -7 + 2x + -2x

Combine like terms: -7x + -2x = -9x
7 + -9x = -7 + 2x + -2x

Combine like terms: 2x + -2x = 0
7 + -9x = -7 + 0
7 + -9x = -7

Add '-7' to each side of the equation.
7 + -7 + -9x = -7 + -7

Combine like terms: 7 + -7 = 0
0 + -9x = -7 + -7
-9x = -7 + -7

Combine like terms: -7 + -7 = -14
-9x = -14

Divide each side by '-9'.
x = 1.555555556

Simplifying
x = 1.555555556

See similar equations:

| p+28=3p | | sqrtx^2+32x=12 | | -24+x=-32 | | 2k+3=2 | | 5n^2=8n+10 | | 180-x=70(2.5) | | 15x-5=-35 | | 5=-3+4x-4 | | 5x-logx=1.62 | | 2(3.14)(3)(7.5)= | | x-9sqrt(x)+14=0 | | 11.2+x-7.6=4.3 | | 2(3.14)(4)(6.5)= | | 3=3x+40 | | 6=6k-5k | | (x+2)(3x+10)=3(m+5)+15 | | x+4sqrt(x)-12=0 | | 9g+5= | | X-9+5x-27=180 | | 356+56+x=-832 | | 0=1-2r-5 | | 6x^2-27y=0 | | 2/9=x/7 | | 14+19=195x | | N/15=2/3 | | 6=5p+p | | 5(x-8)+3x= | | N*6.7=268 | | 3a+8c=43 | | 13x+40=4x+5 | | 7.6a-9.6=1.2a | | 1,-10;m=1/2 |

Equations solver categories